EVALUATION OF COMMUNITY SPRINGS FOR DOMESTIC WATER IN DODA BAHARI VILLAGE, CENTRAL BUTON - IRNAWATI IRUN (Jurnal Belantara, 2026)
This research aimed to evaluate the potential, utilization, maintenance and management of people's springs to ensure their sustainability in Doda Bahari Village, Sangia Wambulu District, Central Buton Regency. Data was collected through field observations, interviews and questionnaires to the community. Data analysis was conducted descriptively to describe the condition of the spring and its level of utilization. The results showed that the area of the spring is 209.14 m2 and the initial utilization was channeled to community homes in 2002, with the condition of vegetation around the spring still dense but sometimes there is logging and the presence of community plantations. In terms of physical parameters, namely smell, taste and color, the people's spring meets the physical parameters for consumption and the discharge obtained is 0.00347 m3/second with water utilization by the community covering domestic needs (drinking, cooking, bathing, washing, toilets and watering plants). The total use of community water is 25,026.6 m3/year, with the smoothness of water received in the community affected by the distance of the spring from the settlement. The main challenges in water utilization are water that does not flow during power outages, reduced discharge during the dry season, water that flows one day and does not flow another day and the presence of lime content when water is cooked based on community interviews. Spring maintenance is good and structural management like reservoir construction has been implemented. However, non-structural management remains suboptimal due to low public awareness and weak village regulations.